Deguelin induced differentiation of mutated NPM1 acute myeloid leukemia in vivo and in vitro. Issue 7 (August 2017) - Zhang, Xia; Zhao, Zichu; Yi, Sha; Wen, Lu; He, Jing; Hu, Jingyu; Ruan, Jun; Fang, Jun; Chen, Yan
Abstract : Nucleophosmin (NPM1), a restricted nucleolar localization protein, shuttles between the nucleus and the cytoplasm. Mutated (Mt)-NPM1 protein, which has aberrant cytoplasmic dislocation of nucleophosmin, occurs in approximately one-third of acute myeloid leukemia cases. Deguelin, a rotenoid isolated from several plant species, is a strong antitumor agent. NOD/SCID mice xenografted with human Mt-NPM1 OCI/AML3 cell lines served as in-vivo models. Wright–Giemsa staining and flow cytometry analysis were used for differentiation assays. Associated molecular events were assessed by western blot and histological analyses. Kaplan–Meier estimates were used to calculate survival. Deguelin toxicity in mice was assessed by immunohistochemistry staining and serum markers. Clinical samples were differentiated by flow cytometry analysis. Deguelin induced differentiation by downregulating the Mt-NPM1 protein levels, which was accompanied by a decrease in SIRT1, p21, and HDAC1 and an increase in CEBPβ and granulocyte colony-stimulating factor receptor protein expression levels. A low-deguelin dose prolonged survival compared with the control group, and there were no apparent lesions to the brain, liver, heart, and kidney in vivo . In clinical samples, deguelin induced the differentiation of fresh blasts with Mt-NPM1 protein, but not with the wild-type NPM1 protein. Taken together, these findings further provide new evidence that the Mt-NPM1 protein plays an important role in inducing differentiation in vivo and in vitro . Mutated NPM1 protein may be a therapeutic target of deguelin in acute myeloid leukemia with the NPM1 mutation. Abstract : Supplemental Digital Content is available in the text.